Curriculum, Political Participation, and Career Choice - Li, Hongbin; Luo, Sai; Wang, Yang (The Review of Economics and Statistics, 2025)
We examine the causal impact of ideological education on students' political participation and career choices by exploiting China's staggered rollout of a high school curriculum reform that emphasized political indoctrination. Using nationally representative survey data on college students that the authors collected, we find that exposure to the new curriculum increases the likelihood of joining the Chinese Communist Party by 14% and raises the probability of securing state-sector jobs after graduation by 15%. These results highlight the powerful role of ideological education in shaping students' political alignments and career trajectories.